STRATEGI HUMAS LAZIS AL IHSAN DALAM MENARIK MUZZAKI MELALUI PROGRAM SEDEKAH SUBUH - Irvan, Irvan Afrizal Pratama (JURNAL KOMUNITAS, 2023)
Lazis Al Ihsan Surakarta has zakat and alms fundraising program, namely the sedekah subuh program. This Program aims to provide a forum for muslims in Surakarta to distribute zakat, infaq, and alms funds. This study used descriptive qualitative research with data collection methods of interviews and documentation. The study aimed to explain Lazis Al Ihsan's public relation strategy for attracting muzzaki through the sedekah subuh program. The results were that the strategy carried out by Lazis Al Ihsan Surakarta in attracting muzzaki through the sedekah subuh program used 4 (four) steps, namely fact finding, and feedback carried out by Lazis Al Ihsan Surakarta to find facts before conducting socialization, planning, and programming to determine steps to be taken before carrying out socialization, action, and communication to carry out socialization activities for the sedekah subuh program. Lazis Al Ihsan Surakarta conducted socialization through various media such as social media (official website, radio broadcasts, WhatsApp) and print media (flyers, brochures). Evaluation was carried out every three months by Lazis Al Ihsan by collecting the relevant coordinators.